Global temperature calibration of the Long chain Diol Index in marine surface sediments. (April 2020) - de Bar, Marijke W.; Weiss, Gabriella; Yildiz, Caglar; Rampen, Sebastiaan W.; Lattaud, Julie; Bale, Nicole J.; Mienis, Furu; Brummer, Geert-Jan A.; Schulz, Hartmut; Rush, Darci; Kim, Jung-Hyun; Donner, Barbara; et al.
Highlights: The core-top LDI-temperature calibration is re-evaluated and extended. Scatter is caused by freshwater and diol contributions from Proboscia diatoms. New constraints on the application of the LDI proxy are proposed. Abstract: The Long chain Diol Index (LDI) is a relatively new organic geochemical proxy for sea surface temperature (SST), based on the abundance of the C30 1, 15-diol relative to the summed abundance of the C28 1, 13-, C30 1, 13- and C30 1, 15-diols. Here we substantially extend and re-evaluate the initial core top calibration by combining the original dataset with 172 data points derived from previously published studies and 262 newly generated data points. In total, we considered 595 globally distributed surface sediments with an enhanced geographical coverage compared to the original calibration. The relationship with SST is similar to that of the original calibration but with considerably increased scatter. The effects of freshwater input (e.g., river runoff) and long-chain diol contribution from Proboscia diatoms on the LDI were evaluated. Exclusion of core-tops deposited at a salinity < 32 ppt, as well as core-tops with high Proboscia -derived C28 1, 12-diol abundance, resulted in a substantial improvement of the relationship between LDI and annual mean SST. This implies that the LDI cannot be directly applied in regions with a strong freshwater influence or high C28 1, 12-diol abundance, limiting the applicability of the LDI. The final LDI calibration (LDI = 0.0325 × SST + 0.1082; R 2  = 0.88; n  = 514) is not statistically different from the original calibration of Rampen et al. (2012) (https://doi.org/10.1016/j.gca.2012.01.024 ), although with a larger calibration error of 3 °C. This larger calibration error results from several regions where the LDI does not seem to have a strong temperature dependence with annual mean SST, posing a limitation on the application of the LDI.